Advances in Urban Lifestyle and Technology. - Suparta, Wayan (Cambridge Scholars Publisher, 2021)
Cities, with all their complexities, grow as engines of development, especially in the fields of sociology, economy, and technology. As they shape the character of people, smart cities that implement strategies for sustainable urban development are a necessity. This book addresses various issues concerning urban lifestyle phenomena affecting the social economy and technological needs such as governance of sustainable urban development, green technology, and the environment. It will be a useful reference for local stakeholders when making appropriate policy and planning choices to protect the e.
Keywords: City planning.; Sustainable urban development.; Green technology.; Urbanisme durable.; Technologie de protection de l'environnement.; Urban communities.; Sustainability.; Social issues: environment & green issues (Children's / Teenage).; City planning; Green technology; Sustainable urban development